The Labor Movement of Matamoros: From Labor Spring to “The Movement is Outside the Union” - Quintero Ramírez, Cirila (2025)
This article analyzes the labor mobilization of Matamoros, Tamaulipas, Mexico, as the resurgence of labor action in Mexico, based on the recovery of a labor identity and a potential for latent protest; as well as, the use of new fighting strategies and the participation of new actors, within a context of political opportunities favorable for worker participation. However, although this mobilization led to the obtaining of immediate economic demands, it was incapable of transforming the local unionism and the labor structure and culture.  The article exemplifies through the National Independent Union of Industrial and Service Workers, “Movimiento 20-32” (SNITIS), considered the emblematic union of the Matamoros labor struggle, the strengths and weaknesses of the labor movilization.